Line mixing study on the fundamental rovibrational band of nitric oxide near 5.3 μm. (February 2022) - Su, Wey-Wey; Boulet, Christian; Almodovar, Christopher A.; Ding, Yiming; Strand, Christopher L.; Hanson, Ronald K.
Highlights: Measured nitric oxide absorption from 1700 to 2000 cm − 1 at 293–802 K, 20–34 atm. Revealed breakdown of a superposition of Lorentzian profiles due to line mixing. Constructed a Modified Exponential Gap inter-branch line mixing model. Explored an alternative modeling approach in the absence of broadening parameters. Found reasonable agreement between an Energy Corrected Sudden model and data. Abstract: In this work, we report quantitative absorbance measurements of nitric oxide (NO) diluted in nitrogen between 1700 to 2000 cm − 1 and present three line mixing modeling approaches for the measured spectra. Static cell measurements were taken using a narrow-linewidth, external-cavity quantum-cascade laser at temperatures of 293 K and 802 K and pressures of 20–34 atm. The measured results exhibit considerable deviations from the spectra simulated by a superposition of Lorentzian line profiles due to significant line mixing coupling effects at high-number-density conditions. Our previous work demonstrated a line mixing model based on relaxation matrix theory and the Modified Exponential Gap (MEG) law for the NO R-branch. With expanded access to the P- and Q-branches, the measured data indicated significant line mixing effects between lines of different branches in addition to those within the same branch. An empirical two-scaling-factor inter-branch MEG model is presented that delivers strong agreement across the measured spectra, with residuals less than 2% for the spectrum at 293 K and 34 atm. In addition, the Energy Corrected Sudden (ECS) scaling law is shown to produce reasonable agreement across the measured spectra, excluding the Q-branch. In the Q-branch peak, the ECS model overpredicts the measured data by about 7%. The different line mixing models presented and discussed in this work will improve NO absorption predictions vital for laser absorption applications in high-number-density gas conditions. Future studies may seek to account for inter-spin-split coupling to further improve the ECS application to NO absorption.